2013
DOI: 10.1017/jrr.2013.6
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Investigation of the Process of Perspective Taking in Interpersonal Situations

Abstract: The ability to take the perspectives of others is considered a pre-requisite for effective interpersonal interaction. Despite extensive investigation into the correlates of perspective taking, there have been few previous attempts to understand the process by which people take another's psychological point of view. The purpose of this exploratory study was to identify the strategies used by individuals when attempting to take the perspective of another person.Twelve participants discussed a time they engaged i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 42 publications
3
46
0
1
Order By: Relevance
“…In a recent qualitative study, Gerace, Day, Casey, and Mohr (2013) asked participants to reflect on the strategies they used in attempting to take the perspective of another person. Amongst the strategies discussed (e.g., imagining oneself in the other's position, considering common responses to certain types of situation), past experiences were commonly used to understand the other person.…”
Section: Paused Hoping He'd Make a Tiny Connection Between His Ownmentioning
confidence: 99%
See 4 more Smart Citations
“…In a recent qualitative study, Gerace, Day, Casey, and Mohr (2013) asked participants to reflect on the strategies they used in attempting to take the perspective of another person. Amongst the strategies discussed (e.g., imagining oneself in the other's position, considering common responses to certain types of situation), past experiences were commonly used to understand the other person.…”
Section: Paused Hoping He'd Make a Tiny Connection Between His Ownmentioning
confidence: 99%
“…For example, participants in the studies by Gerace et al (2013) and Van Boven and Loewenstein (2003) either explicitly referred to past experiences they used to take another's perspective, or demonstrated the ability to reflect upon their similar past experiences when asked. Hodges and Wegner (1997) have also suggested that the empathy experience involves "such a generalized structural transformation in thought and emotion that it must be conceptualized more broadly than many less sweeping changes in mental content" (p. 312), with the implication that "empathy is a state of our minds upon which we can reflect" (p. 313).…”
Section: Similar Past Experience and Ease Of Perspective Takingmentioning
confidence: 99%
See 3 more Smart Citations